Recommendations from the European working group for value assessment and funding processes in rare diseases (ORPH-VAL) - Annemans, Lieven; Schlander, Michael (Orphanet journal of rare diseases, 2017)
Rare diseases are an important public health issue with high unmet need. The introduction of the EU Regulation on orphan medicinal products (OMP) has been successful in stimulating investment in the research and development of OMPs. Despite this advancement, patients do not have universal access to these new medicines. There are many factors that affect OMP uptake, but one of the most important is the difficulty of making pricing and reimbursement (P&R) decisions in rare diseases. Until now, there has been little consensus on the most appropriate assessment criteria, perspective or appraisal process. This paper proposes nine principles to help improve the consistency of OMP P&R assessment in Europe and ensure that value assessment, pricing and funding processes reflect the specificities of rare diseases and contribute to both the sustainability of healthcare systems and the sustainability of innovation in this field. These recommendations are the output of the European Working Group for Value Assessment and Funding Processes in Rare Diseases (ORPH-VAL), a collaboration between rare disease experts, patient representatives, academics, health technology﻿ assessment ﻿(HTA) practitioners, politicians and industry representatives. ORPH-VAL reached its recommendations through careful consideration of existing OMP P&R literature and through a wide consultation with expert stakeholders, including payers, regulators and patients. The principles cover four areas: OMP decision criteria, OMP decision process, OMP sustainable funding systems and European co-ordination. This paper also presents a guide to the core elements of value relevant to OMPs that should be consistently considered in all OMP appraisals. The principles outlined in this paper may be helpful in drawing together an emerging consensus on this topic and identifying areas where consistency in payer approach could be achievable and beneficial. All stakeholders have an obligation to work together to ensure that the promise of OMP's is realised.
Published: 10 March 2017
Gesehen am 19.06.2018